Electronic structures and optical properties of Fe/Co–doped cubic BaTiO3 ceramics. Issue 5 (1st April 2019) - Ma, Yanan; Chen, Huanming; Pan, Fengchun; Chen, Zhipeng; Ma, Zhi; Lin, Xueling; Zheng, Fu; Ma, Xiaobo
Abstract: The electronic structures and the optical properties of Fe/Co–doped cubic BaTiO3 ceramics in which the Ti sites replaced partly and uniformly by Fe or Co chemical elements have been investigated using first–principles method based on the density functional theoretical framework. The calculated energy band structures indicate that Fe/Co–doped cubic BaTiO3 system has electrically conductivity while the purely BaTiO3 features the characteristic of semi–conductivity. In consistent with the energy band structures, some new peaks correlated to the impurity bands have arisen in the total density of state of the Fe/Co–doped BaTiO3 system due to the 3d orbital of Fe/Co atoms making an evidently contribution and a strong orbital hybridization incurred by d–d interaction and p–d interaction near the Fermi energy level being introduced by Fe/Co–doping. The analysis of optical properties, including the calculation of dielectric function, reflection spectrum and absorption spectrum of Fe/Co–doped BaTiO3 system, implied that their photoelectric properties can be improved by Fe/Co–doping due to the required activation energy for the photoelectron transition being reduced effectively. These phenomena such as red–shift phenomenon, the bridge effect of impurity bands and the strong orbital hybridization suggested that they can be as a potentially candidate for optoelectronic materials applied in the field of energy conversion.